Gambaran Excessive Daytime Sleepiness Mahasiswa Keperawatan Tingkat Akhir - Firdausa Aminah Maharani; Artika Nurrahima (Holistic Nursing and Health Science, 2020)
Introduction: Excessive Daytime Sleepiness (EDS) was complained by nursing students last semester that can lead to worse health conditions, decreased learning ability, mood disorders, and motor vehicle accidents. The description of EDS prevalence is the basis of preventive efforts to prevent further effects of EDS which can affect quality of life. Research on the description of EDS based on the characteristics of respondents (age, sex, smoking, duration of sleep, consumption of sleeping pills, consumption of coffee, use of gadgets, and physical activity) has never been done. The purpose of this study was to determine the description of EDS of the final semester nursing students at a university.Methods: This research was descriptive quantitative research with survey method. The sample used was 109 respondents with a total sampling technique. Data collection online used an Epworth Sleepiness Scale (ESS) questionnaire. Data analysis was performed univariate to explain the overview of EDS in the form of frequency and percentage distributions.Results: The results showed that 40.4% of respondents experienced EDS with an ESS score ≥ 10. The incidence of EDS was more experienced by respondents aged 22 years (25.7%), women who were not menstruating (32.7%), did not smoke (38.5%), sleep duration 6-9 hours/day (32.1%), did not consume sleeping pills (40.4%), did not consume coffee (31.2%), used gadgets (38.5%), and physical activity < 3 times a week (23.7%).Conclusion: Students should pay attention to the need for sleep and avoid the factors that cause EDS to improve quality of life, optimize health and avoid the risk of accidents.